2014
DOI: 10.1167/iovs.14-13980
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes in Treated Bacterial Keratitis: Four Years of Prospective Follow-up

Abstract: Cases of bacterial keratitis may continue to demonstrate improvements in visual acuity up to 12 months following diagnosis, but further improvements are unlikely. These findings may guide the appropriate timing of surgical intervention in these patients. (ClinicalTrials.gov number, NCT00324168.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The visual outcome associated with treatment success seems to be good for the less severely affected eyes. A follow-up over a longer duration would be interesting to determine whether there is ongoing reduction in corneal opacity, as described in human bacterial keratitis (McClintic et al 2014). In the current study, one dog was presented with a corneal perforation on the location of a previous deep stromal ulcer 1 month after healing.…”
Section: Discussionmentioning
confidence: 99%
“…The visual outcome associated with treatment success seems to be good for the less severely affected eyes. A follow-up over a longer duration would be interesting to determine whether there is ongoing reduction in corneal opacity, as described in human bacterial keratitis (McClintic et al 2014). In the current study, one dog was presented with a corneal perforation on the location of a previous deep stromal ulcer 1 month after healing.…”
Section: Discussionmentioning
confidence: 99%
“…Scarring in this location has the potential to cause substantial visual loss, even if the infecting organism is successfully eradicated. 75 Although some bacteria (e.g., Neisseria gonorrhoeae) can invade an intact corneal epithelium, most cases of bacterial keratitis develop at the site of an abnormality or defect in the corneal surface.…”
Section: Natural Historymentioning
confidence: 99%
“…For a subset of 50 patients from the original SCUT study, visual outcomes at 4 years have been reported. 39 Twenty-four of these patients were in the corticosteroid group and 26 in the placebo arm. Visual acuity improved most during the first 3 weeks of treatment (by 2.9 lines) and then continued to improve slowly over the first year.…”
Section: Topical Corticosteroids: a Controversial Issuementioning
confidence: 99%